Primary Immature Teratoma of the Uterus Relapsing as Malignant Neuroepithelioma: Case Report and Review of the Literature. (4th June 2013) - Ben Ameur El Youbi, Meryam; Mohtaram, Amina; Kharmoum, Jinane; Aaribi, Imane; Kharmoum, Saoussane; Bouzoubaa, Abdelilah; M'rabti, Hind; Boutayeb, Saber; El Khannoussi, Basma; Errihani, Hassan
Abstract : Background. Although some mature cases of teratomas have recently been described in the cervix, they are not commonly found in the uterus, especially in immature forms. An immature uterine teratoma relapsing after surgery as malignant neuroepithelioma has never been reported in the literature. Case Presentation. We describe a case of immature teratoma which occurred primarily in the uterus in a 56-year-old female. Treatment consisted of total simple hysterectomy. Three months after surgery, the patient relapsed with voluminous pelvic mass and was treated with bleomycin, etoposide, and cisplatin-containing chemotherapy regimen. Conclusion. In this report and according to the pertinent literature, clinical and pathological features and management of uterine immature teratomas are discussed. The mainstay of treatment is surgery. The prognosis of this unusual disease remains uncertain.